2016
DOI: 10.1101/gad.275453.115
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of cancer driverMLL2results in transcription stress and genome instability

Abstract: Genome instability is a recurring feature of tumorigenesis. Mutation in MLL2, encoding a histone methyltransferase, is a driver in numerous different cancer types, but the mechanism is unclear. Here, we present evidence that MLL2 mutation results in genome instability. Mouse cells in which MLL2 gene deletion can be induced display elevated levels of sister chromatid exchange, gross chromosomal aberrations, 53BP1 foci, and micronuclei. Human MLL2 knockout cells are characterized by genome instability as well. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 60 publications
5
83
1
Order By: Relevance
“…In fact, γ-H2AX modification is strongly diminished over highly transcribed genes in yeast (Lee et al, 2014) and we achieved much higher transcription levels with the mAIRN CD cells than with the mAIRN HO cells (Figure 1C). Studies with human cells, however, suggest γ-H2AX can still be enriched at highly expressed regions on the genome (Kantidakis et al, 2016; Tuduri et al, 2009), so our data may be explained by less stably assembled chromatin on the plasmid than on the genome.…”
Section: Discussioncontrasting
confidence: 55%
“…In fact, γ-H2AX modification is strongly diminished over highly transcribed genes in yeast (Lee et al, 2014) and we achieved much higher transcription levels with the mAIRN CD cells than with the mAIRN HO cells (Figure 1C). Studies with human cells, however, suggest γ-H2AX can still be enriched at highly expressed regions on the genome (Kantidakis et al, 2016; Tuduri et al, 2009), so our data may be explained by less stably assembled chromatin on the plasmid than on the genome.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, we identified four genes (MLL2, SUGP2, TP53 and TTN) with recurrent functional mutations in the comparison of superficial tumor tissues with normal tissues. MLL2 is a histone methyltransferase that is part of a large protein complex, ASCOM, that regulates transcription of the β-globin and estrogen receptor genes [13], and recent evidence indicates that MLL2 mutations result in genomic instability, which is a strong driver of tumorigenesis [14]. In our study, we found that 2/3 subjects harbored a frameshift deletion in MLL2, indicating that MLL2 probably also plays a role in tumorigenesis in BCa.…”
Section: Discussionsupporting
confidence: 50%
“…Despite the hope for new targeted therapies, mechanisms for resistance to inhibitors of BET (31, 47, 48) or ATR (18) have been recently uncovered. Interestingly, perturbing the chromatin-related functions of MLL proteins has been shown to lead to DNA replication stress (33, 49). In this context, a combination of RSR inhibitors, leading to p53-independent toxicity, and epigenetic inhibitors that may both interfere with the transcriptional properties of the MLL fusion protein and further increase the levels of replication stress, could help overcome the resistance of MLL-driven AML to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%